Understanding the mechanisms of biological struvite biomineralisation. (October 2021) - Leng, Yirong; Soares, Ana
Abstract: The mechanisms of struvite production through biomineralisation were investigated for five microorganisms ( Bacillus pumilus, Brevibacterium antiquum, Myxococcus xanthus, Halobacterium salinarum and Idiomarina loihiensis ). After 72–96 h of incubation, the microbial strains tested increased the solution pH from 7.5 to 7.7 to 8.4–8.7, and removed ortho -phosphate (63–71%) and magnesium (94–99%) by biomineralisation. The minerals formed were identified as struvite (i.e. bio-struvite). Within the initial 24 h of incubation, microbial growth rates of 0.16–0.28 1/h were measured, and bio-struvite production was observed when the solution supersaturation index with respect to struvite achieved 0.6–0.8 units. The crystals produced by B. pumilus, H. salinarum and M. xanthus were thin trapezoidal-platy shaped and presented a gap size about 200 μm for intervals between cumulative volume undersize distribution at 50% and 90%. While B. antiquum and I. loihiensis produced crystals of coffin-lid/long-bar shape and a narrow size gap around 100 μm for intervals between cumulative volume percentage of 50% and 90%, indicating homogeneous crystal size distribution. Intracellular supersaturation of struvite phase was achieved within B. antiquum and I. loihiensis cells, corresponding to observation of intracellular vesicle-like structures occupied with electron-dense granules/materials. This study suggests that B. antiquum and I. loihiensis produced bio-struvite through biologically controlled mineralisation. This mechanism is the preferred for recovering nutrients from streams such as wastewater because it allows a link between manipulation of microbial growth conditions and bio-struvite production, even in highly complex streams like wastewater. Highlights: Microbial strains reduced SIstruvite for bio-struvite heterogeneous nucleation. The shapes of bio-struvite crystals varied with microbial strains. H. salinarum, B. pumilus and M. xanthus produced bio-struvite by BIM. B. antiquum and I. loihiensis produced bio-struvite by BCM.